Incidence and Outcomes for Patients With Cirrhosis Admitted to the United Kingdom Critical Care Units*. Issue 5 (May 2018) - McPhail, Mark J. W.; Parrott, Francesca; Wendon, Julia A.; Harrison, David A.; Rowan, Kathy A.; Bernal, William
Abstract : Objective: To assess the epidemiology and outcome of patients with cirrhosis following critical care unit admission. Design: Retrospective cohort study. Setting: Critical care units in England, Wales, and Northern Ireland participating in the U.K. Intensive Care National Audit and Research Centre Case Mix Programme. Patients: Thirty-one thousand three hundred sixty-three patients with cirrhosis identified of 1, 168, 650 total critical care unit admissions (2.7%) admitted to U.K. critical care units between 1998 and 2012. Interventions: None. Measurements and Main Results: Ten thousand nine hundred thirty-six patients had alcohol-related liver disease (35%). In total, 1.6% of critical care unit admissions in 1998 had cirrhosis rising to 3.1% in 2012. The crude critical care unit mortality of patients with cirrhosis was 41% in 1998 falling to 31% in 2012 ( p < 0.001). Crude hospital mortality fell from 58% to 46% over the study period ( p < 0.001). Mean(SD) Acute Physiology and Chronic Health Evaluation II score in 1998 was 20.3 (8.5) and 19.5 (7.1) in 2012. Mean Acute Physiology and Chronic Health Evaluation II score for patients with alcohol-related liver disease in 2012 was 20.6 (7.0) and 19.0 (7.2) for non–alcohol-related liver disease ( p < 0.001). In adjusted analysis, alcohol-related liver disease was associated with increased risk of death (odds ratio, 1.51 [95% CI, 1.42–1.62; p < 0.001]) with a year-on-year reduction in hospital mortality (adjusted odds ratio, 0.95/yr, [0.94–0.96, p < 0.001]). Conclusions: More patients with cirrhosis are being admitted to critical care units but with increasing survival rates. Patients with alcohol-related liver disease have reduced survival rates partly explained by higher levels of organ failure at admission. Patients with cirrhosis and organ failure warrant a trial of organ support and universal prognostic pessimism is not justified. Abstract : Supplemental Digital Content is available in the text.